2016
DOI: 10.3389/fpsyg.2016.01474
|View full text |Cite
|
Sign up to set email alerts
|

Classroom-Based Physical Activity Breaks and Children's Attention: Cognitive Engagement Works!

Abstract: Classroom-based physical activity breaks are postulated to positively impact children's attention during their school day. However, empirical evidence for this claim is scarce and the role of cognitive engagement in enhancing children's attentional performance is unexplored in studies on physical activity breaks. The aim of the present study was therefore to disentangle the separate and/or combined effects of physical exertion and cognitive engagement induced by physical activity breaks on primary school child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
155
2
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(195 citation statements)
references
References 84 publications
(138 reference statements)
5
155
2
14
Order By: Relevance
“…Another possible explanation could be the required instructional task, a variable not assessed in the current study. In a previous study that compared cognitive engagement versus physical engagement, student heart rates were higher when they were physically active during a cognitive task (such as what student participants in the present study were often asked to do with in-class assignments) compared to students who were completing a cognitive task with no physical exertion (Schmidt, Benzing, & Kamer, 2016). It is possible that there were more instructional demands on students at the beginning of the intervention and that the difficulty of these cognitive tasks may have decreased over time.…”
Section: Discussionmentioning
confidence: 73%
“…Another possible explanation could be the required instructional task, a variable not assessed in the current study. In a previous study that compared cognitive engagement versus physical engagement, student heart rates were higher when they were physically active during a cognitive task (such as what student participants in the present study were often asked to do with in-class assignments) compared to students who were completing a cognitive task with no physical exertion (Schmidt, Benzing, & Kamer, 2016). It is possible that there were more instructional demands on students at the beginning of the intervention and that the difficulty of these cognitive tasks may have decreased over time.…”
Section: Discussionmentioning
confidence: 73%
“…In summary, this is the first experiment to include objective measurements of both physical activity and learning outcomes in preschool children's science learning. It adds to the existing body of research indicating how physical activity interventions can positively affect cognitive functioning and academic performance in children (Diamond, ; Diamond & Lee, ; Schmidt, Benzing, & Kamer, ; Vazou, Pesce, Lakes, & Smiley‐Oyen, in press). The effects are more pronounced when these interventions include cognitively engaging activities during learning.…”
Section: Discussionmentioning
confidence: 99%
“…Again, less focus has been paid to the qualitative characteristics of the physical activity. However, Schmidt et al (2016) highlighted the promising effects of a cognitively engaging 6-week physical activity intervention in promoting executive functions independently of the exercise intensity. Furthermore, Chang et al (2013) found a positive effect on measures of cognitive functioning of an 8-week intervention focusing on coordinative demanding intensity-independent physical activity.…”
Section: Introductionmentioning
confidence: 99%